Human response to characteristic sound of drones - Aalmoes, R.; Sieben, N.R. (University of Salford, 2024)
New aircraft mobility concepts feature the operation of drones close to locations where humans reside. Main applications currently include photography and video recording and hobbyists operating drones, but observation, inspection and package delivery are expected to become important future applications using drones. Residents close to operations of drones, will therefore be impacted by the increase of the sound events of these vehicles, either by larger drones and thus higher sound levels, or by the increased number of movements, or by both. Since the characteristics of drone sounds are different from other air vehicles, such as helicopters or airplanes, annoyance response is also expected to be different, even at similar loudness levels, as seen in recent studies where drones were considered more annoying than helicopters. Human perception studies with simulations of single event flyover sounds of drones and other vehicles provide insight into a human’s reaction to these vehicles. A new perception study using both visual and auditory stimuli has been performed with similar peak sound levels for flyover events of different vehicles. The results of this study show that both aircraft and drones are rated louder in rural environments than in urban environments. Also, aircraft flyovers are considered more annoying than drone flyovers. No significant difference has been found between drones and helicopter flyovers. But with same peak sound level, drones are perceived significantly louder than Pipistrel Electro aircraft. Some of these results differ from earlier findings, possibly because of other sound characteristics, operational procedures, or different background environments.